Price expectations and the demand for agricultural loans - Habibullah, Muzafar Shah (1985)
Separate studies on the formation of price expectations of future prices of agricultural commodities and the demand for loans have been extensive. However, studies on how farmers form their expectations on future prices of t he agricultural commodities as their decision variable when borrowing decision is made has been neglected. Therefore, the objective of this study is to determine how farmers or farm-firms forms their expectations about price at the time when borrowing decision is made. The study is also aimed at determining other factors that influence the demand for agricultural loans.